Productivity of Oil Palm in Palm Oil Mill Effluent, Empty Bunch and Non-Application Block Areas - Sihite, Yudha Van Heidel; Jaya, Galang Indra; Rochmiyati, Sri Manu (Jurnal Biologi Tropis, 2024)
Oil palm plants are commodities that are mostly processed to produce CPO (Crude Palm Oil) and PKO (Palm Kernel Oil), processing plants also produce waste (by product). The highest waste produced is liquid waste (POME) around 65% and empty palm bunches around 23%. In an effort to reduce environmental pollution, the company is committed to implementing zero waste by reusing palm oil mill waste as organic fertilizer. Research with the aim to determine the effect of the application of palm oil mill effluent, empty fruit bunches, and non-application (inorganic fertilizer) was conducted at the Sungai Rungau Estate (SRGE) plantation, PT Binasawit Abadi Pratama, East Kotawaringin Regency, Central Kalimantan, from November 2023 - April 2024. The research used a survey method to describe the research site and collect primary and secondary data, with each application consisting of 3 blocks. Production data and agronomic characters obtained were then analyzed using t test at 5% level. The results revealed that the application of POME resulted in higher agronomic and production characteristics than tankos. Oil palm production in blocks applied with POME and inorganic fertilizers showed values that were not significantly different and higher than tankos application blocks, and POME application showed productivity that tended to be stable every year.